JINGLE TRANSFORMASI PEGADAIAN (STUDI TENTANG PERAN MUSIK DALAM PEMBENTUKAN BUDAYA PERUSAHAAN PT. PEGADAIAN) - Harimas Jati Wikananta; Ananto Sabdo Aji; Purwa Askanta (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
"Jingle Transformasi Pegadaian” is the title of a song that was employed as one of many transformation tools in PT Pegadaian (Persero). This study aims to determine the existence of “power” that helped the transformation process in PT Pegadaian (persero). To study the phenomenon this research applies mixed methods research design, which consists of ethnographic and quantitative methods. The research data were derived from in-depth interviews and random sampling questionnaire which was distributed to 390 employees in all work units. The process of jingle composing and the elements in the jingle, such as arrangement, genre, lyrics, and vocals were reviewed and perceived as an interpretation of the transformation process that happened in PT Pegadaian (Persero). Messages related to transformation that is contained in the jingle’s lyrics were accepted, and used as an affirmation of the transformation process by all employees. The jingle internalization process is carried out by playing it continuously in all work units’ corporate activities, both routinely and incidentally. The result of this research shows that by playing the jingle continuously forms a “power” that affects the emotional response of employees, and evoke positive reactions, such as: a sense of enthusiasm, awareness of the transformation process, sense of pride, and sense of belonging.